THE IMPACT OF SOWING DATES AND VARIETIES ON THE INCIDENCE OF OXYCARENUS LAETUS AND DYSDERCUS KOINGII ON COTTON - Rafiq Shahid, Muhammad; Mahmood, Abid; Farooq, Jehanzeb; Tasdeeq Hussain Shahid, Muhammad; Asif, Muhammad; Ramzan, Muhammad; Akram, Muhammad; Shahid Iqbal, Muhammad (Comunicata Scientiae, 2014)
Dusky bug (Oxycarenus laetus) and red cotton bugs (Dysdercus koingii) are commonly known as seed bugs because they feed on cotton seed. They have become major threat to cotton in Pakistan since last two years. The present studies were therefore planned to find out the role of sowing dates in cotton pest population. The dusky and red cotton bug population varied considerably with respect to date of sowing. The results revealed that invasion of both bugs was significantly more in case of early sowing ( up to 15 red cotton bug/plant & 25 dusky bugs/boll) than in normal and late sowing (8 to 10 red cotton bugs & 10 to 12 dusky bug/boll respectively). Sampling dates exhibited that population of cotton bugs (dusky and red cotton bug) was higher during first week of October followed by mid September, 2013, whereas lower in late sowing. Varietal comparison depicted that FH-118 and FH-142 showed non significant difference for red and dusky cotton bug population. The results further explained that peak population of red cotton bug was recorded during the month of October, 2013.